Isolation And Screening Of Specific Methicillin Resistant-Staphylococcus Aureus Bacteriophage From Hosiptal Waste At Banyumas - Chairunisa Fadhilah; Saefuddin Aziz; Hendro Pramono (UNEJ e-Proceeding, 2016)
The incidence of infections caused by Methicillin-resistant Staphylococcus aureus (MRSA) were increasing in many hospitals around the world every year. The use of antibiotics therapy became ineffective to control MRSA infection, because it was resistant to methicillin and many beta-lactam class of antibiotics. The use of bacteriophage as biological control agent was a promising strategy to control MRSA. Bacteriophage could infect specific bacteria and destroy their cells. Bacteriophages were found widespread in nature. The aim of this research were to isolate MRSA bacteriophages from hospital waste at Kabupaten Banyumas, and screen specific MRSA bacteriophages.The method was survey by using purposive random sampling to take the soil from waste management installation at Kabupaten Banyumas. Bacteriophages were isolated from the soil by bacteriophage particles precipitation technique and plaque assay. Isolated bacteriophages were henceforth tested for their specificity against MRSA and other pathogenic bacteria. Parameters that were observed encompass the presence of plaque, specific MRSA bacteriophages. Data were analyzed descriptively to interpret the presence of plaque bacteriophages, and the ability of bacteriophage to infect specific host cell (MRSA). The result reveals that the MRSA bacteriophages could be isolated from the hospital sewage, and found two types of bacteriophages were specific MRSA bacteriophages and unspecific MRSA bacteriophage.